2022
DOI: 10.1007/s11119-022-09950-y
|View full text |Cite
|
Sign up to set email alerts
|

Early yield prediction in different grapevine varieties using computer vision and machine learning

Abstract: Yield assessment is a highly relevant task for the wine industry. The goal of this work was to develop a new algorithm for early yield prediction in different grapevine varieties using computer vision and machine learning. Vines from six grapevine (Vitis vinifera L.) varieties were photographed using a mobile platform in a commercial vineyard at pea-size berry stage. A SegNet architecture was employed to detect the visible berries and canopy features. All features were used to train support vector regression (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Palacios et al [145] studied this modeling step in detail and reported (1) 86% recall and 62.2% precision for visible berry detection and (2) 26% Normalized RMSE, R² = 0.82, for actual berry counting with a Support Vector Regression model with features based on fruit area and occlusion. This work was extended to yield prediction [146]. Different methods for image-based yield estimation are detailed and compared in the next section.…”
Section: Performance Comparisonmentioning
confidence: 99%
See 1 more Smart Citation
“…Palacios et al [145] studied this modeling step in detail and reported (1) 86% recall and 62.2% precision for visible berry detection and (2) 26% Normalized RMSE, R² = 0.82, for actual berry counting with a Support Vector Regression model with features based on fruit area and occlusion. This work was extended to yield prediction [146]. Different methods for image-based yield estimation are detailed and compared in the next section.…”
Section: Performance Comparisonmentioning
confidence: 99%
“…Features related to occlusion and fruit area were used as yield predictors in the work of Palacios et al [145,146]. An error rate for 6 varieties of 29.77% NRMSE (in kg per vine, R 2 = 0.83) was reported with images taken 66 days before harvest.…”
Section: Recent Progress and Problems To Solvementioning
confidence: 99%
“…More recently, a good number of deep learning based detection algorithms have been proposed. Palacios et al (2022) present an early yield prediction system based on berry counting using a SegNet segmentation network to extract features from the bunches and canopy images, such as the number of estimated visible berries, or the ratio of leaves in the detection bounding boxes. The statistics on the variability of the features of the 6 grapevine varieties stresses how cross-variety distribution shifts are significant for learning techniques.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve these goals, remote sensing-based decision support systems (DSSs) are usually established to provide information for differentiated nutrient and water supply, plant protection, and harvest [1]. Among passive devices, RGB, thermal, multispectral, and hyperspectral cameras are the most widespread devices used to receive information about biomass and plant physiology or to predict yield and, moreover, to support microclimatic monitoring and terroir zoning [2][3][4][5][6]. Physical traits of the plants such as size, shape, and color are investigated most frequently on the whole canopy or individual leaves, shoots, and moreover on bunches, berries, or even on seeds or roots.…”
Section: Introductionmentioning
confidence: 99%